Soluble Glycoprotein VI Levels Assessed Locally within the Extra- and Intracerebral Circulation in Hyper-Acute Thromboembolic Stroke: A Pilot Study - Andreas Starke; Alexander M. Kollikowski; Vivian Vogt; Guido Stoll; Bernhard Nieswandt; Mirko Pham; David Stegner; Michael K. Schuhmann (Biomedicines)
Background: Severe acute ischemic stroke (AIS) is mainly caused by thromboembolism originating from symptomatic carotid artery (ICA) stenosis or in the heart due to atrial fibrillation. Glycoprotein VI (GPVI), a principal platelet receptor, facilitates platelet adherence and thrombus formation at sites of vascular injury such as symptomatic ICA stenosis. The shedding of GPVI from the platelet surface releases soluble GPVI (sGPVI) into the circulation. Here, we aimed to determine whether sGPVI can serve as a local biomarker to differentiate between local atherosclerotic and systemic cardiac thromboembolism in AIS. Methods: We conducted a cohort study involving 105 patients undergoing emergency endovascular thrombectomy (EVT) for anterior circulation stroke. First, sGPVI concentrations were measured in systemic arterial plasma samples collected at the ipsilateral ICA level, including groups with significantly (≥50%) stenotic and non-stenotic arteries. A second sample, taken from the intracerebral pial circulation, was used to assess GPVI shedding locally within the ischemic brain. Results: Our analysis revealed no significant increase in systemic sGPVI levels in patients with symptomatic ≥ 50% ICA stenosis (3.2 [95% CI 1.5–5.0] ng/mL; n = 33) compared with stroke patients without significant ICA stenosis (3.2 [95% CI 2.3–4.2] ng/mL; n = 72). Additionally, pial blood samples, reflecting intravascular molecular conditions during collateral flow, showed similar sGPVI levels when compared to the systemic ICA samples in both groups. Conclusions: Our findings indicate that GPVI is not locally cleaved and shed into the bloodstream in significant amounts during hyper-acute ischemic stroke, neither at the level of symptomatic ICA nor intracranially during collateral blood supply. Therefore, sGPVI does not appear to be suitable as a local stroke biomarker despite strong evidence of a major role for GPVI-signaling in stroke pathophysiology.